Safety in machinery design and construction: Knowledge and performance. (April 2015) - Bluff, Elizabeth
Highlights: The paper examines safety knowledge which shapes firm performance for safety. Learning through practice is the principal means for constructing safety knowledge. Regulatory and specialist sources are minor constituents of safety knowledge. Certain practices, qualifications and experience sustain better safety performance. There is a need to build safety capacity through a practice-based approach. Abstract: This paper examines how contextualised knowledge about safety matters shaped the performance of machinery manufacturers for three substantive safety outcomes – hazard recognition, risk control and safety information. These issues were investigated in qualitative research with 66 Australian firms that designed and constructed machinery for supply into local and international markets. The paper identifies the constituents of safety knowledge, and clarifies the relatively minor roles of regulatory sources (Australian and European) and the specialist body of knowledge (human factors/ergonomics, safety engineering), compared with learning about safety through design and construction activities and interactions (learning through practice). Individual factors also played a role as key decision makers had diverse professional and vocational (trade) backgrounds, and personal histories from which to interpret their experiences. Certain practices and individual factors sustained better performance for the substantive safety outcomes. The paper makes conceptual contributions to explain the construction of safety knowledge, drawing on established theories of learning (social constructivism) and decision making (bounded rationality), and concludes with some strategic directions for building capacity through practice-based programs which structure opportunities to learn about safety around authentic design and construction activities.